Desarrollo de un videojuego educativo para la presentación de un proyecto escolar de 8vo año de educación general básica - Chiliguana Arévalo, Erika Estefanía (2023)
The advancement of science and technology allows us to improve learning in educational institutions since educational video games have become an innovative and exciting tool that allows the presentation of school projects in which students collaborate, investigate, solve problems, and apply their knowledge; therefore, it has revolutionized how we learn and adapt to different learning styles in an increasingly digitalized world. Educational video games are an essential element in the daily lives of children and young people; that is why teachers adopt this new way of promoting learning and enriching the experience through cognitive, social, and emotional skills in the classroom. The objective of this research proposal is to develop an educational video game to present a school project for the 8th year of junior High School. The SCRUM methodology was used to create an educational video game due to its flexibility and adaptability of the work process. It is formulated in five phases: initialization, planning and estimation, implementation, review and retrospective, and launch. Therefore, educational video games tend to be highly attractive and motivating for students since having a wide range of applications allows their personal development and problemsolving in various areas. Therefore, the educational video game created in this study could serve as an inspiring model for creating other games that address various academic topics and skills in future research. However, it is vital to guarantee adequate teacher training to use this tool effectively.